Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1039/c9cc00097f
|View full text |Cite|
|
Sign up to set email alerts
|

Room-temperature phosphorescent γ-cyclodextrin-cucurbit[6]uril-cowheeled [4]rotaxanes for specific sensing of tryptophan

Abstract: The room temperature phosphorescence of iodine-substituted-γ-CD-CB[6]-cowheeled[4] rotaxanes was quenched specifically by tryptophan among plasma amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…The plots of ln(θ 0 /θ t ) against time gave straight lines, supporting the first-order kinetic model [25]. Increasing the temperature usually increases the reaction kinetics, and we have demonstrated that the temperature is critical for affecting the molecular recognition and stereoselectivity of supramolecular photochirogenesis [26][27][28][29][30][31][32][33]. To understand the temperature effect on the racemization of BP-f1, the CD ex versus time was recorded at different temperatures.…”
Section: Bp-f1supporting
confidence: 66%
“…The plots of ln(θ 0 /θ t ) against time gave straight lines, supporting the first-order kinetic model [25]. Increasing the temperature usually increases the reaction kinetics, and we have demonstrated that the temperature is critical for affecting the molecular recognition and stereoselectivity of supramolecular photochirogenesis [26][27][28][29][30][31][32][33]. To understand the temperature effect on the racemization of BP-f1, the CD ex versus time was recorded at different temperatures.…”
Section: Bp-f1supporting
confidence: 66%
“…At 298 K, two broad signals were observed for the aromatic protons of the biphenyl units of the two [5]catenanes at about δ =7.5 ppm and 7.6 ppm. Because of the asymmetry of the β‐CD, four sets of coupled doublets are expected for the aromatic protons of the included biphenyl when the β‐CD is relatively static . If the β‐CD is able to exchange its position, in the slow exchange regime, multiple sets of signals are to be expected.…”
Section: Resultsmentioning
confidence: 99%
“…Room-temperature phosphorescence (RTP) emitted by purely organic molecules has been attracting increasing attention owing to its advantages over fluorescence, such as longer lifetime, larger Stokes shift, and the involvement of triplet states 1 6 . Such phosphorescent materials have therefore been widely used in organic light-emitting diodes 7 , 8 , data-security 9 , 10 , sensing 11 , 12 , and bioimaging 13 , 14 applications, among others. RTP is usually achieved by means of crystalline packing 15 , 16 or by embedding phosphors in a rigid matrix 9 , 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Macrocyclic compounds (i.e., cyclodextrin, cucurbituril) have become a research hotspot for realizing purely organic phosphorescence in aqueous solution due to their special properties of internal hydrophobicity/external hydrophilicity and host-guest interactions 12,[26][27][28][29][30][31][32] . Up to now, although the phosphorescence in water has made great progress through the host-guest interactions, the purely organic phosphorescence with long lifetime and function in water is rarely reported and still faces great opportunities and challenges.…”
mentioning
confidence: 99%